Effect of feed restriction and supplemental dietary fat on gut peptide and hypothalamic neuropeptide messenger ribonucleic acid concentrations in growing wethers - Relling, Alejandro Enrique (2010)
The objectives of the present study were 1) to evaluate the effects of supplemental fat and ME intake on plasma concentrations of glucagon-like peptide-1 (GLP-1), cholecystokinin (CCK), glucose-dependent insulinotropic polypeptide, ghrelin, and oxyntomodulin; and 2) to determine the association of these peptides with DMI and the hypothalamic concentration of mRNA for the following neuropeptides: neuropeptide Y (NPY), agouti-related peptide (AgRP), and proopiomelanocortin (POMC). In a completely ran domized block design with a 2 × 2 factorial arrangement of treatments, 32 pens with 2 wethers each were restricted-fed (2.45 Mcal/lamb per day) or offered diets ad libitum (n = 16) with or without 6% supplemental fat (n = 16) for a period of 30 d. Dry matter intake was measured daily. On d 8, 15, 22, and 29, BW was measured before feeding, and 6 h after feeding, blood samples were collected for plasma measurement of insulin, GLP-1, CCK, ghrelin, glucose-dependent insulinotropic polypeptide, oxyntomodulin, glucose, and NEFA concentrations. On d 29, blood was collected 30 min before feeding for the same hormone and metabolite analyses. At the end of the experiment, wethers were slaughtered and the hypothalami were collected to measure concentrations of NPY, AgRP, and POMC mRNA. Offering feed ad libitum (resulting in greater ME intake) increased plasma insulin and NEFA concentrations (P = 0.02 and 0.02, respectively) and decreased hypothalamic mRNA expression of NPY and AgRP (P = 0.07 and 0.02, respectively) compared with the restricted-fed wethers. There was a trend for the addition of dietary fat to decrease DMI (P = 0.12). Addition of dietary fat decreased insulin and glucose concentrations (P < 0.05 and 0.01, respectively) and tended to increase hypothalamic mRNA concentrations for NPY and AgRP (P = 0.07 and 0.11, respectively). Plasma GLP-1 and CCK concentrations increased in wethers offered feed ad libitum compared with restricted-fed wethers, but the response was greater when wethers were offered feed ad libitum and had supplemental fat in the diet (fat × intake interaction, P = 0.04). The prefeeding plasma ghrelin concentration was greater in restricted-fed wethers compared with those offered feed ad libitum, but the concentrations were similar 6 h after feeding (intake × time interaction, P < 0.01). Supplemental dietary fat did not affect (P = 0.22) plasma ghrelin concentration. We conclude that insulin, ghrelin, CCK, and GLP-1 may regulate DMI in sheep by regulating the hypothalamic gene expression of NPY, AgRP, and POMC.